Keuangan Syariah Dalam Praktek Arisan: Meningkatkan Pemahaman Pada Komunitas Ikatan Keluarga XIII Koto Kampar - Mairiza, Diany; Rahmawati, Rahmawati; Assyifa, Zubaidah; Irmawanti, Irmawanti; Putri, Berliana (Journal of Community Sustainability, 2025)
This community service activity was carried out for members of the Family Association Community XIII Koto Kampar, Riau Province, where the purpose of this community service is to provide provisions in increasing understanding related to Sharia finance about arisan practices that are in accordance with the principles of Sharia economics to the community, especially members of the Family Association Community XIII Koto Kampar. The methods used in this community service activity are through counseling and presentations, discussions and exercises for participants. The counseling method is used to explain the importance of knowing the concept of Sharia economics about arisan practices that are in accordance with Sharia principles for members of the Family Association Community XIII Koto Kampar. The presentation method is used to show a work process, namely the stages of how we can become individuals who have a prosperous economy. While the question and answer method is used to give participants the opportunity to consult in understanding further the material that has been given. The exercise method is used to see how far the participants understand the service before and after the material is delivered. The availability of adequate experts in delivering this material, the enthusiasm of the participants, and the principal's support for the implementation of the activity are the supporters of the implementation of this PPM activity. The obstacles faced are that the community service participants do not yet have initial knowledge about the material on the concept of the practice of arisan in accordance with sharia and limited time in delivering the material. The results of this service show that: The community service program can be organized well and run smoothly according to the activity plan that has been prepared, the results of this service concluded that: First, Most of the community service participants do not yet understand well the concept of the practice of arisan in accordance with sharia, Second, The achievement of the objectives of the community service program to the participants of the entire program that has been carried out with collaboration between the community and the servants has been carried out all and in accordance with the event rounddown and the time that has been previously determined.